2012
DOI: 10.1186/1471-2393-12-2
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine use during pregnancy assessed by hair analysis in a Canary Islands cohort

Abstract: BackgroundDrug use during pregnancy is difficult to ascertain, and maternal reports are likely to be inaccurate. The aim of this study was to estimate the prevalence of illicit drug use among pregnant women by using maternal hair analysis.MethodsA toxicological analysis of hair was used to detect chronic recreational drug use during pregnancy. In 2007, 347 mother-infant dyads were included from the Hospital La Candelaria, Santa Cruz de Tenerife, Canary Islands (Spain). Data on socioeconomic characteristics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 35 publications
3
21
1
1
Order By: Relevance
“…However, gestational drug use underreporting showed by maternal interview was lower in the study of Pichini et al on 830 mother-infants dyads (2.5% self reporting vs 10.7% meconium testing) [9]. Another study performed by Joya et al [30] on 347 mother-infant dyads in a Canary Island (Tenerife, Spain) using hair analysis showed positive results only for cocaine with prevalence of cocaine of 2.6%. In addition, the authors reported an association between cocaine use during pregnancy and antidepressant use [30].…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…However, gestational drug use underreporting showed by maternal interview was lower in the study of Pichini et al on 830 mother-infants dyads (2.5% self reporting vs 10.7% meconium testing) [9]. Another study performed by Joya et al [30] on 347 mother-infant dyads in a Canary Island (Tenerife, Spain) using hair analysis showed positive results only for cocaine with prevalence of cocaine of 2.6%. In addition, the authors reported an association between cocaine use during pregnancy and antidepressant use [30].…”
mentioning
confidence: 88%
“…Another study performed by Joya et al [30] on 347 mother-infant dyads in a Canary Island (Tenerife, Spain) using hair analysis showed positive results only for cocaine with prevalence of cocaine of 2.6%. In addition, the authors reported an association between cocaine use during pregnancy and antidepressant use [30]. Similarly, Lendoiro et al compared maternal interview and maternal hair analysis in 209 pregnant women in order to determine drug consumption throughout pregnancy and to study the relationship between maternal interview, hair test results, and neonatal outcome [54].…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Erroneous and biased interpretations of the literature can often affect educational programs and even lawsuits. (4) There are deficiencies in the embracement of drug users, because when the social and cultural context in which the individual is inserted is recognized, it becomes possible to identify risk factors that permeate the dysfunctional use of drugs, a fundamental step for the creation of strategies for health teams with families and people in vulnerable situations. (5) Early diagnosis favors intervention and enables access to specialized treatment services and alternatives to deal with drug abuse during pregnancy and/or reducing complications for the mother and the newborn.…”
Section: Introductionmentioning
confidence: 99%